Quality learning and teaching with sessional staff : systematising national standards : final report. - Harvey, Marina (Dept of Education and Training Australia, 2017)
Final report of a Teaching Fellowship at Macquarie University. This Fellowship identified quality learning and teaching with sessional staff as an educational issue, noting that the majority of teaching in Australian universities is undertaken by sessional staff, yet they have been at the periphery of learning and teaching plans. This Fellowship addressed the issue of systematising good practice for learning and teaching with sessional staff through engagement with national standards across the higher education sector.